Periodontitis Kronis Disertai Kebiasaan Mengunyah Satu Sisi (Laporan Kasus) - Ruslim, Andre Kusuma; Azizah, Siti Nur; Dihin, Nuryanni (Mulawarman Dental Journal, 2021)
Background: Periodontitis is an infectious disease on the periodontal tissue caused by specific microorganisms namely periodontopatogen bacteria which results in inflammation and the occurrence of progressive damage. Aim: Periodontitis can be a matching picture of alveolar bone morphology so that there is a decrease in bone height. The pattern of bone damage can be horizontally, vertically, crater seen from radiology, the pathogenesis of this change is important for the enforcement of diagnosis and treatment. Horizontal bone resorption is the peak of alveolar bone decreases, but the remaining bone margin is perpendicular to the surface of the teeth. Vertical / angular bone resorption occurs in the direction of the Oblique, making a hole penetrating into the bones along the roots; Basic damage is located in the apical direction around the bone. Case discussion: of this case report is to explain the bone damage that can occur in periodontitis and determine the pattern of bone damage from radiographs. There are 2 cases of patients with a chronic diagnosis of periodontitis, vulnerable to ages 24 and 48 years, the depth of 3-4 mm pocket on anteroposterior maxilla & mandible, with vulnerable plaque values of index 57.4% and 84% and OHI-S 2.9 and 3.6 (moderate-poor) and panoramic radiographic examination. Conclusions: on this case report pattern of bone damage in patients with chronic periodontitis is seen horizontally and vertically in the case  Radiology Case 1 while in the case of radiology Case 2 is only visible bone damage patterns horizontally.